Bilayer Dissolving Microneedles Incorporating Hypericin-Loaded Nanocapsules For Improved Localised Photodynamic Therapy - Heba M. Abd-; Ismaiel Tekko; Alyaa Ramadan; Noha Nafee; Nawal Khalafallah; Ryan F Donnelly (University of Huddersfield Press, 2019)
Hypericin (Hy) is a potent lipid-soluble photosensitizer having broad pharmacological spectrum. Nevertheless, its poor water solubility leads to its aggregation in the biological systems that consequently diminishes its photodynamic activity (PDA) and its therapeutic applications. Therefore, this study presents novel hydro-solving bilayer microneedle (MN) arrays incorporating Hy-loaded lipid nanocapsules (LNC) to prevent drug aggregation, enhance its delivery and local PDA. The Hy-LNC were prepared by phase inversion technique and showed homogenous particle size distribution and high encapsulation efficiency (88.42 ± 0.11%). The bilayer MNs consist of a hydrogel cross-linked, drug-free base plate and a Hy-loaded MN for a one-step application. The dissolving MNs were fabricated from aqueous blends of 10% w/w polyvinyl alcohol and 30% w/w polyvinyl pyrrolidone by casting and pressure. The MN arrays were characterized for mechanical strength and insertion depth. The bilayer arrays showed good mechanical strength under a compression force of32 N, with a height reduction of 10.14 ± 0.55% and sufficient insertion depth in both Parafilm M® and the excised porcine skin. After 2h of application to excised pig skin, the MNs were completely dissolved ensuring the delivery of its payload and the base plate was removed intact free from MN residuals. Inconclusion, the incorporation of Hy-LNC into this novel bilayer MNs overcome its aggregation and ensured the complete insertion of the drug-loaded MNs. This LNC-MN system is promising for improving Hy local availability and thus enhancing its photodynamic application.